Psychological, cognitive, and physiological impact of hazards casualties' trainings on first responders: the example of a chemical and radiological training. An exploratory study - Giaume, Louise; Le Roy, Barbara; Daniel, Yann; Lauga Cami, Heloise; Jost, Daniel; Travers, Stéphane; Trousselard, Marion (Frontiers in Psychology, 2024)
Background First responders are among the first to respond to hazards casualties. They might operate in volatile, uncertain, complex, and ambiguous (VUCA) environments. While they have underlined the need to improve their knowledge and training to face these environments, there are few data regarding the stress induced by these trainings. Chemical, biological, radiological, and nuclear (CBRN) hazards casualties' trainings seem to be a good model of “in vivo” stress. First responders must operate in a hostile and encountered environment with a CBRN protective equipment that places demand on their psychological, cognitive, and physiological capacities. Current research recognizes that the activity of the parasympathetic system (PSS) can be used as an objective marker of stress adaptation, measured as heart rate variability (HRV). Objectives To compare between baseline and simulation the evolution of the parasympathetic activity (primary outcome), anxiety, emotions, cognitive load, and body posture awareness (secondary outcomes). Methods A total of 28 first responders attended to three simulated scenarios requiring CBRN management of casualties. One day before simulation, we collected HRV data (baseline). The simulations' day (pre-, post-simulation) we collected anxiety score (STAI-Y B), emotions (SPANE), cognitive load (NASA TLX), body posture awareness (PAS) and HRV. The morning after we collected the PAS score (recovery). We compare data' evolution between different times of the simulation. Results (i) A high level of anxiety at baseline [Median 51 (46; 56)] which decreased between pre- and post-simulation (p = 0.04; F = 2.93); (ii) a post-simulation decrease in negative feelings (p = 0.03); (iii) a decrease in body awareness after simulation which returned to the initial level at recovery (p = 0.03; F = 3.48); (iv) a decrease in mean RR between baseline, pre- and post-simulation (p = 0.009; F = 5.11). There were no significant difference between times on others analysis of HRV. Conclusion Prior to simulation, participants experienced anticipatory anxiety. Simulations training practiced regularly could be one way to combat anticipatory anxiety.